Pengaruh Kompensasi Finansial, Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Indofood CBP Sukses Makmur.Tbk Divisi Noodle Pabrik Surabaya Beji Pasuruan - Nunuk Indarti; Siti Nur Khamidah; Etta Mamang Sangadji (MAMEN: Jurnal Manajemen, 2023)
This study aims to develop the discipline of human resource management and as material for further relevant studies as material for study and elaboration of financial compensation, work motivation and work environment on employee performance. The research design in this study uses a quantitative approach with descriptive research methods to determine the effect of compensation. Financial, Work Motivation and Work Environment on Employee Performance with proportional random sampling technique, to determine the number of samples, it is calculated using the slovin formula and a sample of 85 respondents is obtained. The results show that partially the three independent variables have a positive effect and significant to employee performance, it is known that the financial compensation variable has a t-count value of 3.255, the work motivation variable has a t-count value of 4.351, and the work environment variable has a nil ai t count is 2.933 with a t table value of 1.990. Simultaneously the three independent variables have a significant effect on performance with a significant value of 0.000 <0.05 and F count 11.007 > 2.716.